The legal rights, obligations and liabilities of a hirer under a hire purchase agreement as enforced by the Ministry of Trade And Industries, Malaysia / Md. Salleh Ab. Rahman - Ab. Rahman, Md. Salleh (Faculty of Law, 1985)
"Hire Purchase Agreement " includes a letting of goods with an option to purchase and an agreement for the purchase of goods by instalments (whether the agreement describes the instalments as rent or hire or otherwise), rot does not include any agreement - a) whether the property in the goods comprised therein passes at the time of the agreement or upon or at any time before delivery of the goods; b) under which the person by whom the goods are being hired or purchased is a person who is engaged in the trade or rosiness of selling goods of the same nature or description as the goods comprised in the agreement 4.